THE ROLE OF THE FAMILY IN THE FORMATION OF A SPIRITUAL PERSON - Aliyeva Mohichexra Hasan qizi, (Лучшие интеллектуальные исследования, 2024)
Abstract: In this article, the role of the family in the society, in the education of the child duties of the family and parents, the relationship of parents to each other, adults in the family behavior culture, formation and development of the child in the process of education and information on how to avoid mistakes in raising a child in the family given.